Gambaran C-Reactive Protein (CRP) pada Pasien Diabetes Melitus di RSUD S.K. Lerik Kota Kupang - Ni Ketut Yuliana Sari; Nelci Magdalena Tefa; Adrianus Ola Wuan; Tuppak Sirait (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Diabetes mellitus (DM) is a metabolic disorder characterized by hyperglycemia. Hyperglycemia can cause organ damage, which can affect inflammatory responses such as increased C-Reactive Protein (CRP). CRP is an inflammatory marker synthesized in the liver for monitoring non-specific local and systemic diseases. This study aims to determine the profile of CRP in DM patients at S.K. Lerik General Hospital in Kupang City. The study design is a quantitative descriptive study with a cross-sectional approach. A total of 50 respondents participated in this study, comprising 9 respondents (18%) with type 1 DM and 41 respondents (92%) with type 2 DM. The distribution of respondent characteristics included 24 males (48%) and 26 females (52%). The age range was 17 adults (34%) aged 19–59 years and 33 elderly individuals (66%). Respondents with normal fasting blood sugar levels (70–110 mg/dL) numbered 5 (10%), and those with high levels (>110 mg/dL) numbered 45 (90%). Based on the study results, 5 respondents (10%) had reactive CRP levels, and 45 respondents (90%) had non-reactive levels. Reactive CRP results were found in 3 female (6%) and 2 male (4%), 1 adult (2%) and 4 elderly respondents (8%), and all were classified as having type 1 diabetes.